Reversed-Phase HPLC Determination of Aceclofenac in Bulk Powder and its Pharmaceutical Tablets - CENDIL KUMAR, A.; DEVESWARAN, R.; MADHAVAN, V. (Asian Journal of Chemistry, 2010)
This paper presents a simple accurate, reproducible and rapid RP-HPLC method for estimation of aceclofenac in both bulk powder and its tablet. The analysis was carried out, in isocratic mode, on C18 column. The mobile phase is comprised of acetonitrile: methanol:phosphate buffer pH 7.0 (30:17:53). A stock solution of 1 mg/mL of aceclofenac in mobile phase was prepared and the linearity over a range of 2-10 mcg/mL was examined. The retention time of the drug was 13.8 min. The R2 value of 0.9992 indicates a good linearity in the concentration range of 2-10 mcg/mL. The chromatogram was scanned at 280 nm, which is the absorption maximum of the drug.